(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Daley suggests that although nurses can often feel powerless in moral decision making, they are actually in a strong position to have a direct and positive impact on patient health. This is because patients are the usual focus of the decision, and the final right act is the right act for a particular person in particular circumstances. This is the central element of the principle of double effect, which allows for an action with both a positive and harmful effect provided the intended outcome is good. This principle is often used in an attempt to justify why a certain action was taken and needs to be understood in order to assess the morality of a previous action. Any act considered harmful must have been the least harmful option in comparison to the good outcome. This is often not the case in clinical practice and may be the underlying cause of moral distress. An example from the author’s practice was when an elderly confused patient had continence pads prescribed instead of requesting assistance to the toilet. The nursing team agreed that this intervention would be easier for staff; however, it was recognized that the decision was made in consideration for the patient’s behavior, not his best interest. This caused moral distress for those involved as they felt this was not an advocacy for the patient. Nurses encounter ethical dilemmas in their clinical practice, particularly those associated with taking on a doctor’s role because the need and knowledge for some medical procedures are now within the domain of nursing. Daley suggests that in the absence of a strong professional identity, that is based on a clear definition of the unique role of nursing, many nurses turn to medicine as a reference point for decision making. This can result in moral distress when a nurse knowingly acts in a way that conflicts with their professional values. What is ethics? The term derives from the Greek word "ethicos," which translates to character. This reflects the idea of something being moral as being based on an individual’s character because moral decisions are based on what a person feels is the right thing to do. Daley identifies the understanding of personal and professional values as an integral part of being able to successfully negotiate moral choices. Nursing ethics is a branch of applied ethics that concerns itself with activities in the field of nursing. Nursing ethics shares many principles with medical ethics, such as beneficence, non-maleficence, and respect for autonomy. It can be distinguished by its emphasis on relationships, human dignity, and collaborative care. This paper will explore the importance of nursing ethics in today’s society. It will discuss the characteristics of ethical dilemmas and the various mechanisms that influence the type of ethical decision an individual may make. It will draw on the author’s experiences as a student nurse and will conclude with a concise abstract on this topic.